A comparative study of efficacy of oral pregabalin and clonidine for attenuation of pressor response to intubation - Kaur, Haramritpal; Gupta, Jatin; Singh, Amandeep; Singh, Gurpreet; Dahuja, Anshul; Rajora, Parveen; Rana, Rubina; Baghla, Naresh (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Endotracheal intubation is associated with hemodynamic stress responses. Various drugs have been used in the past to attenuate the pressor response; however, none has been proved to be ideal. Present study was planned to evaluate the oral pregabalin 150 mg and clonidine 200 µg for attenuation of pressor response to intubation. Methods: The study was conducted on 100 adult patients of either gender scheduled to undergo elective surgeries under general anaesthesia (GA). The patients were randomly allocated into 2 groups. In group A patients received pregabalin 150mg and in group B patients received clonidine 200µg orally. The hemodynamic parameters were recorded until 10 minutes after intubation. The sedation, anxiety and side effects were also assessed. Results: In clonidine group, the mean HR remained below the baseline value at all the time intervals. In pregabalin group, the mean HR remained below the baseline value at most of the time intervals but increased above baseline just after intubation (T0i) and 1 minute after intubation (T1i) where increase was only 1.488±1.20% and 0.45±1.16% respectively from baseline. In both pregabalin and clonidine groups, the mean SBP and MAP remained below the baseline value (Tb) at all the time intervals from T0.5 to T10i. Both clonidine and pregabalin provided adequate anxiolysis and sedation with pregabalin providing more pronounced sedation and anxiolysis than clonidine. Conclusions: Both clonidine and pregabalin are effective oral premedication drugs for attenuation of the pressor response to laryngoscopy and endotracheal intubation.